Sistem Monitoring pH Untuk Tanaman Strawberry Dengan Sistem Aeroponik - Moh. Sugeng Irawan; Aries Boedi Setiawan; Rahman Arifuddin (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2021)
Strawberry is a kind of plant that can grow well in the highlands. The cultivation of strawberry plants requires a large area of ​​land, whereas in urban areas the land is increasingly narrow. The best solution to overcome this is by cultivating an aeroponic system. Aeroponic systems utilize the element of water or solution which is sprayed in the form of mist and will hit the roots of plants. The pH monitoring system in strawberry plants is carried out to observe changes in the PH of the water sprayed to the roots of the plants according to the PH requirements of the strawberry plants. The monitoring system using Android with a user interface that is easy to use and PH information of strawberry plants can be easily monitored. At pH, it has an error of 0.33%, while for other tests it has an error of 0.16%. For sending data with the HC05 module testing with a distance of 10 meters and 20 meters the device can be connected properly and data reception is also good. For a distance of 25 meters and 30 meters, there is a delay in the process of receiving data, for testing distances of 35 meters and 40 meters the receipt of data is incomplete and the data displayed is also irregular. Then for testing with a distance of 55 meters an error occurred and a distance of 57 meters could not be connected